Persistence of Soil Enthalpy Drives the Winter and Summer Climate Connection in the Tibetan Plateau - Zouxing Lin; Zhiyan Zuo; Renhe Zhang; Dong Xiao; Qinglong You; Liang Qiao (Geophysical Research Letters)
Abstract Although some outcomes have been reported, our knowledge of the Tibetan Plateau (TP) climate and its prediction remains unclear due to land surface complexity and observational uncertainty. Here, long‐term observations and reanalysis data revealed a significant positive relationship between winter and the subsequent summer surface air temperatures (SATs) over the TP, in which we highlighted the role of the persistence of soil enthalpy (SE) process. The winter SE can memorize the winter SAT anomaly, and the signal decays with depth gradually, but the consistency with spring SE increases substantially. This persistence of the SE process facilitates the winter SAT signals to be preserved for months until summer, resulting in homogeneous SAT anomalies in summer. The atmospheric response to the SAT anomaly further demonstrates the significant effect of winter thermal conditions on the subsequent summer climate over the TP. Hence, this work brings a new perspective for understanding the TP climate.